PENCAPAIAN PEMERINTAHAN ITI OCTAVIA SEBAGAI BUPATI DI LEBAK TAHUN 2014-2018 - Junior Hendri Wijaya (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2019)
This study aims to determine the achievements of the government of Iti Octavia as Lebak Regent in 2014-2018. This research uses a qualitative method with literature study. The results of this study indicate that the achievement of Iti Octavia as Regent of Lebak in 2014-2018 has reached several fields, namely in the field of public services by developing Star Up, in the field of health by adding health facilities in each region and increasing participants of Health Insurance users, in addition in the field of Iti education Octavia has succeeded in improving quality in the Lebak district with the result of decreasing illiteracy rates, as well as increasing gross participation and pure enrollment rates (APK / APM) increasing at all levels of education.